Artificial Intelligence Comic Strips (AICS) for Retelling Students’ Experience: Does It Work and How? - Diana elfira; Faiza Hawa (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
Artificial Intelligence Comic Strips (AICS) is a sophisticated combination of Artificial Intelligence (AI) and Comic Strips (CS). The use of AICS in the learning process can help students improve their skills, particularly in writing recount texts. This research was completed to seek an answer if AICS works for teaching writing and improving students’ abilities in composing written experiences and to know how AICS works for teaching writing. The research used a quasi-experimental design, and the main sample was eighth-graders at SMP Negeri 1 Subah. The instruments used were pre-test, post-test, and questionnaire. Data analysis and processing were done with SPSS 27. The implementation of AICS increased the average score of students in the experimental class from the pre-test score (60.359) to the post-test score (81.550). The Asymp. Sig. (2-tailed) value of 0.000 in the Wilcoxon test indicates a highly significant difference between the pretest and post-test results. The questionnaire given to students was divided into 3 parts: students' initial ability in writing recount text, students' knowledge of AI and comic strips, and students' experience in using AICS. The questionnaire's findings indicated that the students agreed that using AICS was enjoyable, helped them develop ideas, and provided them with optimism that they would get high scores. In conclusion, implementing AICS can help students write recount texts and motivate them to learn.